Promotion and Development of Palm Tree Products to Promote Tourism in Bor Tru Community, Ranod District, Songkhla Province - Bunyarit, Chotipong; Ketphet, Chonthida; Yimprasert, Palat (Parichart Journal, 2025)
This study is applied research employing a mixed-methods approach. The objectives are: (1) to examine community identity and analyze the economic feasibility of promoting tourism in the Not Sin Group; (2) to design products that support tourism promotion in the Not Sin Group; (3) to develop public relations media using marketing strategies to enhance tourism promotion in the Not Sin Group; and (4) to propose guidelines for upgrading and developing sugar palm products for community-based tourism management in Bo Tru Subdistrict, Ranot District, Songkhla Province. The sample consisted of five groups: (1) Not Sin Group (10 participants), (2) Government Agency Group (10 participants), (3) Business Entrepreneur Group (10 participants), (4) Bo Tru Community Village Group (10 participants), and (5) Tourist Group (100 participants). A purposive sampling method was employed. Research instruments included interviews and satisfaction questionnaires. The research steps are: 1) study community identity, 2) design products, 3) design public relations media, and 4) propose guidelines for upgrading and developing sugar palm products for community tourism management. The research findings indicate that the prominent community identity is embodied in the architectural features of Sihyang Temple, Phra Chedi Ngam Temple, Pradu Temple, and Pho (Khae) Temple. This unique architectural identity has been applied to product design in the following forms: 1) Palm-leaf hanging mobile from Pho (Khae) Temple 2) Peacock-inspired photo frame from Sihyang Temple 3) Palmyra palm fruit ice cream from Phra Chedi Ngam Temple 4) Palmyra palm jelly dessert from Pradu Temple. The promotional media developed for this purpose consist of motion graphics and posters, which provide information on travel routes and tourist attractions associated with the four temples. The proposed guidelines for enhancing and developing palmyra palm products to support community-based tourism management are as follows: 1) Establishing creative tourism objectives, particularly in the form of one-day trips 2) Promoting knowledge and understanding among relevant stakeholders 3) Integrating community-based and external activities 4) Ensuring the sustainability and continuity of activities.